Ceramic copper circuit board, semiconductor device, ceramic copper circuit board manufacturing method, and semiconductor device manufacturing method
Patent Information
- Application Number
- JP2024224299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-04-11
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-04-02
Smart Images

Figure 2025038181000001_ABST
Abstract
Description
[Technical field]
[0001] The embodiments generally relate to a ceramic copper circuit board, a semiconductor device, a method for manufacturing a ceramic copper circuit board, and a method for manufacturing a semiconductor device. [Background technology]
[0002] Ceramic copper circuit boards are used in semiconductor devices equipped with semiconductor elements such as power elements. The ceramic substrate and the copper circuit are bonded to each other via a bonding layer. A silver (Ag) brazing material containing active metals such as titanium (Ti) is used for the bonding layer. This improves the bonding strength and heat cycle characteristics. As their reliability has improved, ceramic copper circuit boards are used in automobiles (including electric vehicles), electric railway vehicles, solar power generation facilities, inverters for industrial machines, etc. In semiconductor devices such as power modules, semiconductor elements are mounted on copper circuit parts. In addition, wire bonding and metal terminals may be bonded to the semiconductor elements for electrical continuity. In the manufacture of semiconductor devices, semiconductor elements, wire bonding, metal terminals, etc. are bonded to the copper circuit parts. As power modules become smaller, lighter, and more densely packed, the copper circuit portion is becoming thicker in order to reduce thermal resistance and inductance. A ceramic copper circuit board with a thick copper circuit portion is described in International Publication WO2018-180965 (Patent Document 1). Patent Document 1 improves the assembly of the ceramic copper circuit board by optimizing the number of grain boundaries on the surface of the copper circuit board. The ceramic copper circuit board of Patent Document 1 improves the bonding and alignment accuracy of semiconductor elements. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2018-180965 Summary of the Invention [Problem to be solved by the invention]
[0004] On the other hand, problems that arise from thickening of the copper circuit part other than the above-mentioned bondability or alignment accuracy have become clear. For example, in order to improve the reliability of the product, it is desirable to realize fine patterning of the copper circuit part and stress relaxation of the entire circuit board. In Patent Document 1, the focus is on controlling the grain size on the surface of the copper circuit part, but it has been found that as the copper circuit becomes thicker, a difference occurs between the grain size on the surface and inside. In other words, it is possible to improve the bondability and alignment accuracy of the copper plate surface by controlling the surface of the copper circuit, but it has been found that control of the inside of the copper circuit is necessary to improve other characteristics such as fine patterning. In recent years, power semiconductor modules have become smaller, lighter, and more densely packed. Accordingly, there is a demand for thicker metal circuits to reduce the thermal resistance and inductance of the metal circuits. In addition, there is a demand for finer patterns on the metal circuits to increase the density of the packaging. Furthermore, with the rise in the junction temperature (Tj) of power semiconductor chips, there is also a demand for improved reliability of ceramic circuit boards. The embodiments are intended to solve such problems, and relate to a ceramic copper circuit board that enables finer circuits and improves the reliability of the ceramic circuit board. [Means for solving the problem]
[0005] The ceramic copper circuit board according to the embodiment includes a ceramic substrate, a copper circuit portion provided on the ceramic substrate, and a first bonding layer provided between the ceramic substrate and the copper circuit portion, the first bonding layer including an active metal brazing material component. In a cross section of the copper circuit portion parallel to a first direction from the ceramic substrate toward the copper circuit portion, any line drawn along the first direction intersects with a plurality of copper crystal grains. The average value of a plurality of distances in the second direction between the line and the end of each of the copper crystal grains farthest from the line in a second direction perpendicular to the first direction is 50 μm or more and 300 μm or less. The outer edge of each of the plurality of copper crystal grains includes a first end and a second end that intersect with the line. The maximum value of the length in the first direction between the first end and the second end of each of the plurality of copper crystal grains is 301 μm or more. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 is a diagram showing an example of a ceramic copper circuit board according to an embodiment. [Diagram 2] A diagram showing an example of a cross section of a copper circuit portion [Diagram 3] A diagram showing an example of a cross section of a copper circuit portion [Figure 4] FIG. 1 is a diagram showing an example of pattern dimensions and spacing dimensions of a copper circuit. [Diagram 5] FIG. 1 is a diagram showing an example of a semiconductor device according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The ceramic copper circuit board according to the embodiment includes a ceramic substrate, a copper circuit portion provided on the ceramic substrate, and a first bonding layer provided between the ceramic substrate and the copper circuit portion, the first bonding layer including an active metal brazing material component. In a cross section of the copper circuit portion parallel to a first direction from the ceramic substrate toward the copper circuit portion, any line drawn along the first direction intersects with a plurality of copper crystal grains. The average value of a plurality of distances in the second direction between the line and the end of each of the copper crystal grains farthest from the line in a second direction perpendicular to the first direction is 50 μm or more and 300 μm or less. The outer edge of each of the plurality of copper crystal grains includes a first end and a second end that intersect with the line. The maximum value of the length in the first direction between the first end and the second end of each of the plurality of copper crystal grains is 301 μm or more. FIG. 1 shows an example of a ceramic copper circuit board. In FIG. 1, 1 is a ceramic copper circuit board. 2 is a ceramic substrate. 3 is a copper circuit portion. 4 is a bonding layer containing a brazing material. 5 is a back copper plate. A ceramic substrate 2 has a front surface 2a (first surface) and a back surface 2b. A copper circuit portion 3 is bonded to the front surface 2a of the ceramic substrate 2 via a bonding layer 4 (an example of a first bonding layer). In the example of FIG. 1, a plurality of copper circuit portions 3 are bonded to the front surface 2a via a plurality of bonding layers 4. The embodiment is not limited to the illustrated form. One copper circuit portion 3 or three or more copper circuit portions 3 may be bonded to the front surface 2a. In addition, in the example of FIG. 1, a back copper plate 5 is bonded to the back surface 2b. The back copper plate 5 functions as a heat sink rather than a circuit. The back copper plate 5 is provided as necessary. Instead of the back copper plate 5, a patterned copper circuit portion may be provided on the back surface 2b.
[0008] The ceramic substrate 2 is preferably any one of an aluminum oxide substrate, an aluminum nitride substrate, and a silicon nitride substrate. In addition, an aridil substrate is also available. Aridil is a sintered body that is 20 to 80% aluminum oxide and the remainder zirconium oxide. The three-point bending strength of an aluminum nitride substrate or an aluminum oxide substrate is about 300 to 450 MPa, and the strength of an aluminium substrate is also about 550 MPa. The three-point bending strength of the silicon nitride substrate can be increased to 600 MPa or more, and even 700 MPa or more. The thermal conductivity of the silicon nitride substrate can be increased to 50 W / (m·K) or more, and even 80 W / (m·K) or more. In particular, in recent years, there are silicon nitride substrates that have both high strength and high thermal conductivity. The thickness of the silicon nitride substrate is preferably 0.635 mm or less, and more preferably 0.3 mm or less. Since the silicon nitride substrate has high strength, it can be made thin, and it is possible to improve heat dissipation. There is no particular lower limit for the thickness, but it is preferably 0.1 mm or more. This is to ensure the electrical insulation of the silicon nitride substrate. Here, the thickness refers to the dimension in the direction connecting the ceramic substrate 2 and the copper circuit portion 3. The ceramic copper circuit board according to the embodiment may include one ceramic substrate, or may include two or more ceramic substrates. For example, a plurality of ceramic substrates and a plurality of copper circuit portions may be alternately stacked in the first direction.
[0009] FIG. 2 is a diagram showing an example of a cross section of the copper circuit portion. FIG. 2 is an enlarged cross section of part A of FIG. 1. In FIG. 2, 7 indicates an arbitrary imaginary line. This line is parallel to a first direction from the ceramic substrate 2 toward the copper circuit portion 3. In FIG. 2, D1 indicates the first direction. The line is also perpendicular to the front surface 2a and the back surface 2b. 8 indicates the amount of side etching. The amount of side etching is the distance in one direction perpendicular to the first direction between the outer periphery of the front surface 3a of the copper circuit portion and the outer periphery of the back surface 3b of the copper circuit portion. The copper circuit portion is made of copper polycrystals. The method of drawing the line 7 is as follows. First, the ceramic copper circuit board is cut parallel to the first direction D1. An enlarged photograph of the cross section is taken. At this time, the enlarged photograph is taken at an enlarged scale so that the ceramic substrate is visible and the grain boundaries can be confirmed. Next, the line 7 is obtained by drawing an arbitrary straight line perpendicular to the surface 2a in the enlarged photograph. In addition, if the state of the surface 2a of the ceramic substrate surface is unclear and the back surface 3b of the copper circuit portion 3 can be regarded as a surface parallel to the surface 2a, an arbitrary straight line perpendicular to the back surface 3b may be treated as the line 7. FIG. 3 shows an example of a cross-sectional view of the inside of the copper circuit part. FIG. 3 is an enlarged cross-section of part B in FIG. 2. 10 denotes copper crystal grains, and 11 denotes grain boundaries of the copper crystal grains. In the cross-section of the copper circuit part, an arbitrary line 7 is drawn in a direction perpendicular to the ceramic substrate surface (thickness direction of the substrate). In FIG. 3, 12 denotes a distance LH in the second direction D2 from the arbitrary line 7 to the outer edge (grain boundary 11) of the copper crystal grain 10 farthest from the arbitrary line 7 among the copper crystal grains 10 intersected by the line 7. 13 denotes a length LV between the first end 10a and the second end 10b, which are the intersections of the line 7 and the outer edge of the copper crystal grain 10. The second direction is perpendicular to the first direction and parallel to the cross-section. In the ceramic copper circuit board according to the embodiment, the average distance LH is 300 μm or less, and the average length LV is preferably 300 μm or less. In ceramic copper circuit boards, which are ceramic substrates and ceramic substrates with copper circuit parts bonded to them, a copper plate is bonded to the entire surface or part of the ceramic substrate, and then the copper plate is etched to form the circuit. When dissolving a copper plate by etching, the dissolution proceeds along the crystal grain boundaries of the copper plate. For this reason, the shape of the copper crystal grains has a large effect on the etching. In other words, when the crystal grain size is large, dissolution tends to proceed not only in the thickness direction where the etching solution digs through, but also in the surface direction. The surface direction is the direction perpendicular to the first direction. The second direction is a direction parallel to the surface direction. For multiple copper crystal grains intersecting with a line parallel to the first direction, the average distance LH between them is 300 μm or less, which indicates that copper crystal grains with relatively small dimensions in the second direction are aligned in the thickness direction. This makes it possible to suppress the progress of etching in the surface direction and reduce the amount of side etching due to etching. As a result, it becomes easier to form fine pattern circuits. The fine pattern circuit here refers to a circuit board with a pattern spacing of about 60 to 80% of that of a normal circuit. A fine pattern circuit is one in which at least a part of the circuit satisfies this range of pattern spacing. FIG. 4 shows the pattern dimension 14 and pattern spacing 15 of a ceramic copper circuit board 1. The pattern dimension 14 indicates the width of the electrically conductive portion including the bonding layer 4. The pattern spacing 15 indicates the dimensional distance between the bonding layers 4 formed on the ceramic surface. In the example of FIG. 4, a plurality of copper plates 3 are bonded to the surface 2a of the ceramic substrate 2. The plurality of copper plates 3 are arranged in the second direction D2 and are each bonded to the ceramic substrate 2 via a plurality of bonding layers 4. The distance in the second direction D2 between the bonding layers 4 adjacent to each other in the second direction D2 corresponds to the pattern spacing 15. The pattern width (pattern dimension) is required to be a predetermined value or more for electrical conduction, bonding of semiconductor elements and metal terminals, wire bonding, etc. For example, when the copper plate thickness is 0.1 mm or more and less than 0.5 mm, the pattern dimension is preferably 0.5 mm or more. When the copper plate thickness is 0.5 mm or more and less than 0.7 mm, the pattern dimension is preferably 0.7 mm or more. When the copper plate thickness is 0.7 mm or more and less than 0.8 mm, the pattern dimension is preferably 1.0 mm or more. Here, when the copper plate thickness is 0.1 mm or more and less than 0.5 mm, the pattern spacing dimension is 0.6 mm or more in a normal copper circuit board. In contrast, in a fine pattern circuit, the pattern spacing dimension is 0.4 mm or more. Similarly, when the copper plate thickness is 0.5 mm or more and less than 0.7 mm, the pattern spacing dimension is 1.0 mm or more in a normal copper circuit board. In contrast, in a fine pattern circuit, the pattern spacing dimension is 0.6 mm or more. When the copper plate thickness is 0.7 mm or more and less than 0.8 mm, the pattern spacing dimension is 1.8 mm or more in a normal copper circuit board. In contrast, in a fine pattern circuit, the pattern spacing dimension is 1.1 mm or more. In addition, by setting the average length LV of the copper circuit part to 300 μm or less, the copper plate is easily plastically deformed, which reduces the stress generated in the bonded ceramic copper circuit board, improving the bond strength, board bending strength, and heat cycle resistance, resulting in a highly reliable ceramic circuit board. In addition, in ceramic copper circuit boards, the grain size of the copper plate becomes larger due to the heat treatment during bonding. It is possible to control the coarsening of grain size by adding additives or processing to copper to control the coarsening of grains, and by adjusting the bonding conditions, but this control may increase manufacturing costs. For example, by setting the distance LH and length LV to 50 μm or more, a ceramic copper circuit board with good cost performance can be obtained. However, it is possible to manufacture with a distance LH and length LV shorter than this, and no lower limit is specified. The copper circuit section 3 is bonded to semiconductor elements and the like. In order to reduce thermal resistance and inductance, the thickness of the copper circuit section is preferably 0.5 mm or more, more preferably 0.8 mm or more. In this case, if the average distance LH inside the copper circuit section is small, the amount of side etching is suppressed. This makes it possible to form a fine pattern. In addition, the stress of the bonded body is relieved, thereby improving the bonding strength, the bending strength of the board, and the heat cycle resistance. If the average distance LH inside the copper circuit is greater than 300 μm, the copper crystal grains inside the copper circuit will become larger in the lateral direction, increasing the amount of side etching, which reduces the dimensional accuracy of the circuit pattern. If the average length LV inside the copper circuit is greater than 300 μm, the plastic deformation of the copper circuit will be small, which will result in increased stress in the bonded body and a decrease in properties such as bond strength. Furthermore, if each distance LH and each length LV are adjusted to be smaller than 50 μm, the manufacturing cost increases due to the load caused by process control. Also, even when the average of the distance LH is 300 μm or less, if there are many copper crystal grains whose distance LH is greater than 400 μm, the amount of side etching varies. The distance LH is preferably 400 μm or less. Similarly, even when the average of the length LV is 300 μm or less, if there are many copper crystal grains whose length LV is greater than 400 μm, the bonding strength varies. The length LV is preferably 400 μm or less. As described above, it is preferable that at least one of the average distance LH and the average length LV of the copper crystal grains inside the copper circuit is 300 μm or less. More preferably, it is preferable that both the average distance LH and the average length LV are 300 μm or less. Furthermore, it is preferable that each distance LH and each length LV are 400 μm or less. In this case, it is preferable that each distance LH is 50 μm or more. It is preferable that each length LV is 50 μm or more. More preferably, each distance LH is 50 μm or more and each length LV is 50 μm or more. Moreover, each distance LH is preferably 300 μm or less. Each length LV is preferably 300 μm or less. More preferably, each distance LH is 300 μm or less and each length LV is 300 μm or less. In this case, each distance LH is preferably 70 μm or more. Each length LV is preferably 70 μm or more. More preferably, each distance LH is 70 μm or more and each length LV is 70 μm or more. In the ceramic copper circuit board according to the embodiment, when any straight line is drawn along the first direction on the cross section of the copper circuit portion 3, the distance LH and length LV of the multiple copper crystal grains intersecting with the line are within the above-mentioned ranges. In other words, no matter where the straight line is drawn on the cross section of the copper circuit portion 3, the distance LH and length LV are within the above-mentioned ranges. By forming a circuit on the ceramic substrate using this copper circuit portion 3, excellent reliability can be obtained.
[0010] When the copper circuit part is formed by processing a copper plate, the crystal size may be adjusted in the rolling process to adjust the thickness of the copper plate, thereby adjusting the distance LH and the length LV. It is also possible to adjust the crystal size by adding a small amount of element to the copper plate. At this time, it is also possible to add a small amount of an element that controls grain growth, such as tin (Sn) or zirconium (Zr), to the copper plate in advance. In a process such as bonding when manufacturing a ceramic copper circuit board, it is also possible to diffuse an element that suppresses grain growth in the copper plate into the copper plate. Furthermore, a heat treatment process during the manufacturing process of the ceramic copper circuit board may be used. The recrystallization temperature of copper is about 220°C. As described later, the copper plate is bonded to the ceramic substrate by active metal bonding. In the active metal bonding method, the ceramic substrate and the copper plate are heated at 700 to 900°C. In this process, the copper plate is recrystallized. When recrystallized, the copper crystal grains grow. By controlling this phenomenon, the size of the copper crystal grains can also be adjusted.
[0011] Moreover, the thickness of the copper circuit portion in the first direction is preferably 0.5 mm or more, more preferably 0.8 mm or more. By setting the thickness of the copper circuit portion to the aforementioned value, the effect of fine patterning during etching can be more significantly obtained. That is, the effect of the present invention can be obtained even when the thickness of the copper circuit portion is thinner than the aforementioned value. However, since the difference from products manufactured by conventional manufacturing methods is not large, it is difficult to obtain the effect of the present invention. The thickness of the ceramic substrate is not particularly limited. By making the ceramic circuit substrate thinner and the copper circuit portion thicker, the heat dissipation performance is improved. The upper limit of the thickness of the copper circuit portion is not particularly limited, but is preferably 5 mm or less. If the thickness of the copper circuit portion exceeds 5 mm, warping will be large when bonded by the active metal bonding method. This may make it difficult to make the ceramic substrate thinner.
[0012] Moreover, the ceramic substrate 2 and the copper circuit portion 3 are preferably bonded via a bonding layer 4. Moreover, when a back copper plate 5 is provided, the back copper plate 5 is preferably bonded to the ceramic substrate 2 via a bonding layer. Moreover, a bonding layer containing Ag (silver) and Ti (titanium) is preferably provided between the ceramic substrate and the copper circuit portion. The bonding layer containing Ag and Ti is formed using an active metal brazing material. Ti is an active metal. Other active metals besides Ti include Zr (zirconium). Examples of active metal brazing materials include mixtures of Ti, Ag, and Cu (copper). For example, the Ti content is 0.1 to 10 wt%, the Cu content is 10 to 60 wt%, and the balance is Ag. In addition, when controlling the grain size in the copper circuit part by diffusion of the brazing material during bonding, one or more selected from the group consisting of In (indium), Sn (tin), Al (aluminum), Si (silicon), C (carbon), and Mg (magnesium) may be added at 1 to 15 wt% as necessary. In the active metal bonding method using the active metal brazing material, an active metal brazing material paste is applied to the surface of the ceramic substrate, and a copper plate is placed on top of it. This is heated at 700 to 900°C for bonding. With the active metal bonding method, the bonding strength between the ceramic substrate and the copper circuit part can be 16 kN / m or more.
[0013] Also, a metal thin film mainly composed of one selected from the group consisting of Ni (nickel), Ag (silver), and Au (gold) may be provided on the surface of the copper circuit. Examples of such metal thin films include plated films and sputtered films. By providing a metal thin film, corrosion resistance, solder wettability, and the like can be improved.
[0014] Such a ceramic copper circuit board is suitable for a semiconductor device in which a semiconductor element is mounted on the copper circuit portion via a bonding layer. FIG. 5 shows an example of a semiconductor device. In FIG. 5, 1 is a ceramic copper circuit board. 16 is a semiconductor device. 17 is a semiconductor element. 18 is a bonding layer (an example of a second bonding layer). 19 is a wire bonding. 20 is a metal terminal. In FIG. 5, a semiconductor element 17 is bonded to a copper circuit part of a ceramic copper circuit board 1 via a bonding layer 18. Similarly, a metal terminal 20 is bonded to the bonding layer 18. The semiconductor elements and the copper circuit parts of adjacent copper circuit parts are electrically connected by wire bonding 19. The semiconductor device according to the embodiment is not limited to such a structure. For example, either the wire bonding 19 or the metal terminal 20 may be provided. Also, a plurality of the semiconductor element 17, the wire bonding 19, and the metal terminal 20 may be provided on the copper circuit part 3. Also, the semiconductor element, the wire bonding, or the metal terminal 20 may be bonded to the back copper plate 5 as necessary. Moreover, various shapes such as a lead frame shape and a convex shape can be applied to the metal terminals 20. Solder, brazing material, etc. are used for the bonding layer 18 that bonds the semiconductor element 17 and the metal terminal 20. Lead-free solder is preferable for the solder. Solder refers to solder with a melting point of 450°C or less. Brazing material refers to solder with a melting point of over 450°C. A material with a melting point of 500°C or more is called a high-temperature brazing material. Examples of high-temperature brazing materials include those containing Ag as the main component.
[0015] The ceramic copper circuit board according to the embodiment has an average distance LH of 300 μm or less, and therefore has excellent etching characteristics during circuit formation. In particular, the thicker the copper plate is, such as 0.8 mm or more, the more the side etching characteristics are suppressed, and the more effective the fine pattern formation can be obtained. When the copper plate becomes thick and fine pattern formation is difficult, pattern defects due to etching residue may occur. In addition, measures such as slowing down the etching rate are required to prevent side etching. From this point of view, according to the present embodiment, the reliability of the ceramic copper circuit board can be improved, and the cost performance can be improved.
[0016] The ceramic copper circuit board according to the embodiment has an average length LV of 300 μm or less, so that stress can be alleviated. In the ceramic copper circuit board, residual stress occurs due to the bonding between the copper plate and the ceramic. Furthermore, when a semiconductor element is usually mounted on the copper circuit, stress occurs due to the difference in thermal expansion between the ceramic substrate and the copper circuit caused by heat generated from the semiconductor element. As the grain size in the copper circuit portion becomes smaller in the direction perpendicular to the bonding surface with the ceramic substrate, the stress generated in the copper circuit portion becomes smaller. When the stress is reduced, it is possible to suppress the occurrence of cracks and the like due to the difference in stress between the ceramic substrate and the copper circuit portion even when the thickness of the copper circuit portion is 0.5 mm or more. From this point of view, according to this embodiment, the reliability of the ceramic copper circuit board can be improved.
[0017] In addition, while the miniaturization of semiconductor elements progresses, the amount of heat generated from the chips increases. Therefore, it is important to improve the heat dissipation of ceramic copper circuit boards on which semiconductor elements are mounted. In addition, in order to improve the performance of semiconductor devices (semiconductor modules), multiple semiconductor elements can be mounted on ceramic copper circuit boards. If even one semiconductor element exceeds the intrinsic temperature of the element, the resistance changes to a negative temperature coefficient. As a result, thermal runaway occurs in which power flows intensively, and the semiconductor device is instantly destroyed. Therefore, it is very effective to improve the reliability of the connection between the semiconductor element and the copper circuit part. In addition, the semiconductor device according to the embodiment can be used in PCUs, IGBTs, and IPM modules used in inverters for automobiles (including electric vehicles), electric railway vehicles, industrial machinery, and air conditioners. As for automobiles, electric vehicles are becoming more and more popular. The more the reliability of the semiconductor device improves, the more the safety of the automobile can be improved. The same is true for electric railway vehicles, industrial equipment, and the like.
[0018] Next, a method for producing the ceramic copper circuit board according to the embodiment will be described. The method for producing the ceramic copper circuit board is not particularly limited as long as the ceramic copper circuit board has the above-mentioned configuration. Here, an example of a method for obtaining the ceramic copper circuit board with a high yield will be described. First, prepare a ceramic substrate and a copper plate. The thickness of the copper plate is 0.5 mm or more. The ceramic substrate is preferably one selected from an aluminum oxide substrate, an aluminum nitride substrate, and a silicon nitride substrate. In particular, in consideration of the heat dissipation of the entire circuit board, the ceramic substrate is preferably a silicon nitride substrate having a thermal conductivity of 50 W / (m K) or more and a three-point bending strength of 600 MPa or more. When the copper circuit portion provided on the front surface of the ceramic substrate is electrically connected to the copper back plate provided on the rear surface through a through hole, a ceramic substrate having a through hole is prepared. When the through hole is provided in the ceramic substrate, the through hole may be provided in advance at the stage of the molded body. Also, the through hole may be provided in the ceramic substrate (ceramic sintered body). The through hole is provided by laser processing, cutting processing, etc. An example of the cutting processing is a hole making process using a drill or the like.
[0019] It is preferable to prepare a copper plate in which the average distance LH of the internal copper crystal grains is 300 μm or less when heated under the bonding conditions for ceramics. It is also preferable to prepare a copper plate in which each distance LH is 400 μm or less. Each distance LH is preferably 50 μm or more, and more preferably 70 μm or more. In addition, it is preferable to prepare a copper plate having an average internal copper crystal grain length LV of 300 μm or less when heated under the bonding conditions for ceramics. It is also preferable to prepare a copper plate having each length LV of 400 μm or less. Each length LV is preferably 50 μm or more, and more preferably 70 μm or more. When a ceramic substrate and a copper plate are bonded by an active metal bonding method, the bonding temperature is about 700 to 900°C. When a copper plate is exposed to this temperature, copper recrystallizes, and the crystal grains become larger. It is preferable to use a copper plate containing copper crystal grains with a shorter distance LH and a shorter length LV than the above range so that the distance LH and length LV of the copper crystal grains are within the above range.
[0020] The ceramic substrate and the copper plate are preferably joined by an active metal bonding method. In the active metal bonding method, an active metal brazing material in which an active metal such as Ti and Ag are mixed is used. The active metal brazing material may be a mixture of Ti, Ag, and Cu. In the active metal brazing material, the Ti content is 0.1 to 10 wt%, the Cu content is 10 to 60 wt%, and the balance is Ag. If necessary, one or more elements selected from the group consisting of In, Sn, Al, Si, C, and Mg may be added within the range of 1 to 15 wt%. The active metal brazing material is made into a paste. The paste is a mixture of brazing material components and organic matter. In the paste, the brazing material components are preferably mixed uniformly. This is because if the brazing material components are not distributed uniformly, brazing becomes unstable and causes poor joining. There are various methods for dispersing the brazing material uniformly. Generally, methods for mixing powders can be used, such as dry and wet milling, mixing with a stirrer, and preforming the alloy and then pulverizing it. During brazing, the brazing material diffuses into the copper plate, causing the copper crystal grains to become larger. For this reason, it is preferable to adjust the brazing material during production so that it does not diffuse into the copper plate. Among the brazing material components described above, a combination of Ag and at least one selected from the group consisting of In and Sn is a component that suppresses diffusion. For this reason, the elements contained in the combination are mixed so as to be uniform in the paste. The brazing material components may be mixed for a sufficient amount of time so as to be uniform, or a process may be added to mix the above combination in advance.
[0021] The active metal brazing paste thus produced is applied to a ceramic substrate. A copper plate is placed on the paste. Next, the ceramic substrate on which the copper plate is placed is heated at 700 to 900°C to bond the substrate. The heating step is carried out in a vacuum or in a non-oxidizing atmosphere as required. When the heating step is carried out in a vacuum, the temperature is set to 1×10 -2 The pressure is preferably not more than Pa. Examples of the non-oxidizing atmosphere include a nitrogen atmosphere and an argon atmosphere. By using a vacuum or non-oxidizing atmosphere, the bonding layer can be prevented from being oxidized, which improves the bonding strength. In addition, by adjusting the bonding temperature and time, the diffusion of the brazing material into the copper plate can be controlled. In order to control the diffusion state of the brazing material components into the copper plate, it is preferable to perform a degreasing process of the active metal brazing material paste during the heat bonding process. In the heat bonding process, the bonding temperature is maintained within a range of 700 to 900°C. By degreasing the organic matter in the paste before the temperature reaches this range, the amount of diffusion of the brazing material components into the copper plate can be controlled. This is because degreasing the organic matter in the brazing material paste before bonding can homogenize the brazing material in contact with the copper plate. In the degreasing process of the brazing paste, the temperature is maintained within a range of, for example, 250 to 500° C. The holding time is within a range of 5 to 60 minutes. Alternatively, it is also effective to set the heating rate toward the bonding temperature to 10° C. / min or less.
[0022] The copper plates to be bonded may be either pre-processed into a pattern or may be solid sheets. When a solid sheet is used, it is etched after bonding to process it into the pattern. This process allows the manufacture of a ceramic copper circuit board. Next, a process of bonding a semiconductor element or the like to the ceramic copper circuit board is performed. A bonding layer is provided at the location where the semiconductor element is to be bonded. The bonding layer preferably contains solder or brazing material. The bonding layer is provided, and the semiconductor element is provided thereon. If necessary, a metal terminal is bonded via the bonding layer. If necessary, wire bonding is provided. The required number of semiconductor elements, metal terminals, and wire bonding are provided.
[0023] (Example) (Examples 1 to 22, Comparative Examples 1 to 9) Silicon nitride substrates, aluminum nitride substrates, and aluminum oxide (alumina) substrates were prepared as ceramic substrates. The thermal conductivity of the silicon nitride substrate was 90 W / (m·K), and the three-point bending strength was 650 MPa. The thermal conductivity of the aluminum nitride substrate was 170 W / (m·K), and the three-point bending strength was 300 MPa. The thermal conductivity of the aluminum oxide substrate was 20 W / (m·K), and the three-point bending strength was 350 MPa. The size of the ceramic substrates was 50 mm long and 40 mm wide. The thickness of the silicon nitride substrate was 0.32 mm. The thickness of the aluminum nitride substrate and the alumina substrate were 0.635 mm.
[0024] Next, the copper plates shown in Table 1 were prepared. The copper plates were cut out from the base material to a length of 40 mm x width of 30 mm to be used as test copper plates for measuring the grain boundary horizontal distance and grain boundary vertical distance after heating. The test plate for measurement was heated in a nitrogen atmosphere at 600°C for 1 hour, and then cut in the horizontal direction to a length of 30 mm. The vicinity of the center of the cut test plate (a position about 15 mm from the end) was observed with a scanning electron microscope (SEM) at a magnification of 20 times, and a photograph was taken. Regarding the measurement position in the thickness direction, the entire copper plates 1 to 9 with a thickness of 0.5 mm were measured from the back surface to the front surface. The vicinity of the end in the thickness direction (up to a position about 150 μm from the top and bottom surfaces) of the copper plates 10 to 18 with a thickness of 0.8 mm were measured. The distance LH and length LV of the copper crystal grains in the copper plate were calculated by the following procedure. First, an arbitrary straight line parallel to the first direction was drawn in the observed area. Next, five copper crystal grains intersecting with the line were extracted. The five copper crystal grains were randomly extracted. However, crystal grains cut off at the edge of the observed area were excluded. For each of the five copper crystal grains, the distance LH in the second direction between the arbitrary straight line and the outer edge of the copper crystal grain was measured, and the average value was shown in Table 1 as the distance LH. In addition, for each of the five copper crystal grains, the length LV in the first direction between the intersections between the arbitrary straight line and the outer edge of the copper crystal grain was measured, and the average value was shown in Table 1 as the length LV. [Table 1]
[0025] Next, the ceramic substrate and the copper plate were joined by the active metal joining method. The copper plate used was the same size as the test copper plate for measurement, cut from the base material to 40 mm length x 30 mm width. The active metal brazing material used in the active metal joining method contained 2 wt% Ti, 10 wt% Sn, 30 wt% Cu, and the remainder was Ag. The active metal paste was prepared by preparing a brazing filler metal in which the materials to be used were mixed together (normally mixed), and a brazing filler metal in which Sn and Ag were mixed in advance and then other active metal brazing filler metal components were mixed (premixed), and then mixing the organic components into each to create a paste. The active metal paste was applied to both sides of the ceramic substrate, and a copper plate was placed on each side to carry out the thermal bonding process. The bonding temperature was set to 790 to 850°C, the bonding time was set to 5 to 20 minutes, and the bonding was performed in a vacuum (1×10 -2 The grain growth of the copper crystal grains inside the copper plates was controlled by changing the bonding temperature and bonding time. In addition, the copper plate on the front side (front copper plate) was etched into a circuit shape. The front copper plate was processed into any one of two to four circuit shapes, and the copper plate on the back side (back copper plate) was also etched into a circuit shape. The pattern dimension was 0.5 mm for fine pattern formation on the front copper plate. For the front copper plate with a thickness of 0.5 mm, etching was performed with the pattern spacing set to 0.8 mm when the amount of side etching and the amount of solder protrusion were zero. For the front copper plate with a thickness of 0.8 mm, etching was performed with the pattern spacing set to 1.1 mm when the amount of side etching and the amount of solder protrusion were zero. The front copper plate with a thickness of 0.5 mm and the front copper plate with a thickness of 0.8 mm were etched under the same conditions.
[0026] Under these manufacturing conditions, the premixed paste is more uniformly dispersed than the regular mixed paste, and is therefore able to suppress the growth of copper crystal grains. However, premixing adds an additional step to regular mixing, and as a result, the cost performance of premixing is inferior to that of regular mixing. In addition, with respect to the bonding temperature of 790 to 850° C., a lower bonding temperature can suppress the growth of copper crystal grains. However, as the bonding temperature approaches the lower limit of the bonding temperature, peeling may occur more easily or the bonding strength may decrease. In addition, with regard to the bonding time of 5 to 20 minutes, it is possible to suppress the grain growth of copper with a shorter bonding time. However, the shorter the bonding time, the higher the possibility that the brazing material does not react sufficiently, and the bonding strength may decrease.
[0027] For this reason, in Examples 1 to 22, normal manufacturing conditions (normal mixed paste, bonding temperature 830°C, bonding time 10 minutes) were used for small distance LH and length LV based on the distance LH and length LV measured in Table 1. For large distance LH and length LV, manufacturing conditions that suppress grain growth of copper crystal grains (premixed paste, bonding temperature 790°C, bonding time 5 minutes) were used. In contrast, in Comparative Examples 1 to 3, normal manufacturing conditions (normal mixed paste, bonding temperature 830°C, bonding time 10 minutes) were used for the large distance LH and length LV measured in Table 1. In Comparative Examples 4 to 5, manufacturing conditions (pre-mixed paste, bonding temperature 790°C, bonding time 5 minutes) that suppress the grain growth of copper crystal grains were used for the even larger distance LH and length LV measured in Table 1. In Comparative Examples 6 to 9, manufacturing conditions (bonding temperature 850°C, bonding time 20 minutes) that further promote the grain growth of copper crystals were used. The obtained ceramic copper circuit board is shown in Table 2.
[0028] [Table 2]
[0029] Next, the cross-sectional structure of the obtained sample was observed by SEM, and the distance LH and length LV were measured. Based on the measured distance LH and length LV, distances LH1 to LH4 and lengths LV1 to LV4 were determined. Distance LH1 is the maximum value of the multiple distances LH. Distance LH2 is the average value of the multiple distances LH. Distance LH3 is the minimum value of the multiple distances LH. Distance LH4 is the difference between the maximum value (LH1) and the minimum value (LH3). Length LV1 is the maximum value of the multiple lengths LV. Length LV2 is the average value of the multiple lengths LV. Length LV3 is the minimum value of the multiple lengths LV. Length LV4 is the difference between the maximum value (LV1) and the minimum value (LV3). The results are shown in Table 3.
[0030] [Table 3]
[0031] As can be seen from the table, the distance LH1 and the length LV1 of the ceramic copper circuit board according to the example are within the range of the preferred embodiment. On the other hand, the distance LH1 and the length LV1 of the comparative example are larger than those of the example. Next, the amount of side etching was examined for the ceramic copper circuit boards of the examples and comparative examples. The horizontal distance between the front and back surfaces of the copper circuit part was measured using an optical microscope, and the maximum distance was taken as the amount of side etching. The pattern spacing was measured using a projector, and the distance between the portion of the bonding layer where the side etching amount was measured and another bonding layer adjacent to that portion was measured. In addition, the peel strength was measured as the bonding strength between the copper circuit portion and the ceramic substrate. The peel strength was measured by peeling off the copper circuit portion, which was previously formed to a width of 3 mm, along the first direction at 50 mm / min. In addition, the bonding strength of the ceramic circuit substrate was measured by pressing the ceramic circuit substrate from above and below using a three-point bending jig. Next, the reliability of the ceramic copper circuit boards according to the examples and the comparative examples was evaluated. As the reliability, the bondability of the semiconductor element was evaluated. In this evaluation, samples prepared under the same conditions as in the examples and comparative examples were used for reliability evaluation, rather than samples that had been cut to measure the copper crystal grain size or samples that had been measured for bonding strength or three-point bending strength. The bonding of the semiconductor element was performed by bonding the semiconductor element and the metal terminal using lead-free solder. Furthermore, wire bonding was provided to conduct the semiconductor element and the metal terminal. This resulted in the fabrication of a semiconductor device. Next, a temperature cycle test (TCT) was performed on the semiconductor device to examine the occurrence rate of poor conduction. In the TCT, one cycle was -40°C x 30 minutes → room temperature x 10 minutes → 150°C x 30 minutes → room temperature x 10 minutes, and the peeling area due to cracks after 300 cycles was calculated using an ultrasonic flaw detection method (SAT: Scanning Acoustic Tomograph). Then, the non-peeling area rate η was evaluated. The non-peeling area rate η was defined as η = 100% when no cracks were generated by TCT, and η = 0% when cracks were generated over the entire surface of the joint of the ceramic copper circuit board by TCT. The measurement results are shown in Table 4.
[0032] [Table 4]
[0033] Among the ceramic copper circuit boards according to the embodiment, in those in which both the distance LH2 and the length LV2 were 300 μm or less, when the copper plate thickness was 0.5 mm, the side etching amount was less than 0.10 mm. When the copper plate thickness was 0.8 mm, it was less than 0.20 mm. As the side etching amount decreased, the dimension between patterns became larger. That is, for the ceramic copper circuit board according to the embodiment, even under the same etching conditions as those of the comparative example, the dimension between patterns can be reduced, and a fine pattern can be formed. In addition, due to the effect of stress relaxation of the copper circuit part, the bonding strength was 24 kN / m or more. For the silicon nitride substrate, the three-point bending strength was 600 MPa. For the aluminum nitride substrate, the three-point bending strength was 250 MPa. For the alumina substrate, the three-point bending strength was 300 MPa or more. Thus, according to the embodiment, a highly reliable ceramic copper circuit board was obtained. Furthermore, among the ceramic copper circuit boards according to the embodiments, those in which only either the distance LH2 or the length LV2 was 300 μm or less provided ceramic copper circuit boards with a good amount of side etching, or ceramic copper circuit boards with good bonding strength and three-point bending strength due to stress relaxation. As for the distance LH1 and the length LV1, those satisfying 300 μm or less respectively provided good results. As for the distance LH3 and the length LV3, those satisfying 200 μm or less respectively provided good results. As for the distance LH4 and the length LV4, good results were obtained when they satisfied 220 μm or less. In contrast, in the comparative example, the amount of side etching was large, a state in which the patterns were not formed (short circuit) occurred, and the bonding strength and three-point bending strength were low. From these results, it can be seen that the distance LH and the length LV affect the amount of side etching, bonding strength, and three-point bending strength. In addition, there was a difference in the unpeeled area ratio η between the Example and the Comparative Example. This is because the side etching amount, bonding strength, and three-point bending strength were improved in the Example by controlling the distance LH1 and length LV1 inside the copper circuit. In contrast, in the comparative example, there were cases where the unpeeled area ratio η deteriorated. This is because the distance LH2 and length LV2 of the copper crystal grains in the copper circuit part were large, resulting in a large amount of side etching. In addition, the bonding strength and three-point bending strength decreased, and the thermal stress inside the ceramic copper circuit board increased, resulting in a large load on the bonding part.
[0034] Although some embodiments of the present invention have been illustrated above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. In addition, the above-mentioned embodiments can be implemented in combination with each other. [Explanation of symbols]
[0035] 1…Ceramic copper circuit board 2...Ceramic substrate 3...Copper circuit section (front copper plate) 4...Joint layer (brazing material) 5...Copper circuit section (back copper plate) 6…Cross-section of copper circuit (enlarged view of part A) 7...A line drawn arbitrarily perpendicular to the thickness direction of the board 8…Side etching amount 9…Cross-section of the inside of the copper plate (enlarged view of part B) 10…Copper crystal grain 11...Grain boundary of copper crystal grains 12…Distance (LH) 13...Length (LV) 14...Pattern dimensions 15…Pattern spacing 16...Semiconductor device 17...Semiconductor element 18...Joining layer 19…Wire bonding 20…Metal terminal
Claims
1. A ceramic substrate; a copper circuit portion provided on the ceramic substrate; a first bonding layer provided between the ceramic substrate and the copper circuit portion and containing an active metal brazing material component; Equipped with In a cross section of the copper circuit portion parallel to a first direction from the ceramic substrate toward the copper circuit portion, any line drawn along the first direction intersects with a plurality of copper crystal grains, an average value of a plurality of distances in a second direction between the line and an end of each of the copper crystal grains farthest from the line in a second direction perpendicular to the first direction is 50 μm or more and 300 μm or less; an outer edge of each of the plurality of copper grains includes a first end and a second end that intersect the line; A ceramic copper circuit board, characterized in that the maximum length in the first direction between the first end and the second end of each of the plurality of copper crystal grains is 301 μm or more.
2. 2. The ceramic copper circuit board according to claim 1, wherein the maximum value of the plurality of distances is 400 μm or less.
3. 3. The ceramic copper circuit board according to claim 1, wherein the minimum value of the plurality of distances is 200 μm or less.
4. 4. The ceramic copper circuit board according to claim 1, wherein a difference between the maximum value of the plurality of distances and the minimum value of the plurality of distances is 220 μm or less.
5. 5. The ceramic copper circuit board according to claim 1, wherein an average length in the first direction between the first end and the second end of each of the plurality of copper crystal grains is 300 μm or less.
6. 6. The ceramic copper circuit board according to claim 5, wherein the maximum value of the plurality of lengths is 512 μm or less.
7. 7. The ceramic copper circuit board according to claim 5, wherein the minimum value of the plurality of lengths is 200 μm or less.
8. 8. The ceramic copper circuit board according to claim 5, wherein a difference between a maximum value of the plurality of lengths and a minimum value of the plurality of lengths is 220 μm or less.
9. 9. The ceramic copper circuit board according to claim 1, wherein the ceramic substrate is one of an aluminum oxide substrate, an aluminum nitride substrate, and a silicon nitride substrate.
10. 10. The ceramic copper circuit board according to claim 1, wherein the ceramic substrate has a thickness in the first direction of 0.7 mm or less.
11. The ceramic copper circuit board according to any one of claims 1 to 10, characterized in that the first bonding layer contains at least one of Ti and Zr, and at least one selected from the group consisting of Ag, Cu, Sn, In, Al, Si, C, and Mg.
12. A plurality of the copper circuit portions; a plurality of first bonding layers provided between the ceramic substrate and the plurality of copper circuit portions; Equipped with 12. The ceramic copper circuit board according to claim 1, wherein the minimum distance between adjacent first bonding layers is less than 1.0 mm.
13. 13. The ceramic copper circuit board according to claim 1, wherein the copper circuit portion has a thickness in the first direction of 0.5 mm or more.
14. A ceramic copper circuit board according to any one of claims 1 to 13, a semiconductor element mounted on the copper circuit portion via a second bonding layer; A semiconductor device comprising:
15. An active metal brazing paste is applied onto the ceramic substrate, A copper plate is placed on the active metal brazing paste; The ceramic substrate and the copper plate are bonded to each other by maintaining the bonding temperature in the range of 700 to 900° C. for 5 to 60 minutes. A method for producing a ceramic copper circuit board, comprising the steps of: forming a copper circuit portion by etching the copper plate; In the manufactured ceramic copper circuit board, in a cross section of the copper circuit portion parallel to a first direction from the ceramic substrate toward the copper circuit portion, any line drawn along the first direction intersects with a plurality of copper crystal grains, A method for manufacturing a ceramic copper circuit board, characterized in that an average of multiple distances in a second direction between the line and an end of each of the copper crystal grains farthest from the line in a second direction perpendicular to the first direction is 50 μm or more and 300 μm or less.
16. Implementing the method for producing a ceramic copper circuit board according to claim 15, A method for manufacturing a semiconductor device, comprising mounting a semiconductor element on the copper circuit portion via a second bonding layer.
Citation Information
Patent Citations
Ceramic circuit board and power semiconductor module using it
JP2005268821A
Metal ceramic composite, its bonding method, and heat dissipation substrate using composite
JP2006128286A
Copper alloy with high strength and excellent processability in bending, and its production process
JP2007177274A
Ceramic wiring board and manufacturing method and semiconductor module of the same
JP2011124585A
Oxygen-free copper plate and ceramic wiring board
JP2018204108A